2018
DOI: 10.1080/09593985.2018.1425786
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability of the unsupported upper-limb exercise test (UULEX) and 6-min peg board ring test (6PBRT) in healthy adult individuals

Abstract: UULEX is a reliable test in healthy adults. Only one test is adequate when measuring peak unsupported arm exercise capacity using the UULEX in healthy adults, while more than two tests may be needed to measure arm endurance using the 6PBRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 23 publications
2
23
1
Order By: Relevance
“…The results of this study showed that the UULEX test was a valid and reliable method for the evaluation of upper extremity function and endurance of individuals with RA. In the literature, there are validity and reliability studies of the UULEX test for individuals with COPD and healthy adults, in which the ICC for UULEX intra‐rater reliability ranges from 0.85 to 0.97. In the current study, the intra‐rater reliability values (ICC: 0.92‐0.96) were consistent with data in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of this study showed that the UULEX test was a valid and reliable method for the evaluation of upper extremity function and endurance of individuals with RA. In the literature, there are validity and reliability studies of the UULEX test for individuals with COPD and healthy adults, in which the ICC for UULEX intra‐rater reliability ranges from 0.85 to 0.97. In the current study, the intra‐rater reliability values (ICC: 0.92‐0.96) were consistent with data in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…During the test, a subject can move up to a maximum of a 2 kg bar in a maximum of 12 minutes. The subject is instructed to continue the test until limited by the emergence of symptoms (Figure ). DASH: The DASH questionnaire consists of 30 items; 21 related to daily living activities, five to symptoms (pain, activity‐related pain, tingling, stiffness, weakness), and each of the remaining four items assesses social function, work, sleep and self‐confidence. All items are answered on a 5‐point Likert scale ([a]: no difficulty, [b]: mild difficulty, [c]: moderate difficulty, [d]: excessive difficulty [e]: cannot perform).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations